PROTOTYPE OF TEMPERATURE AND HUMIDITY MONITORING SYSTEM FOR AIR HANDLING UNIT (AHU) BASED ON BLYNK AT JUWATA TARAKAN AIRPORT - Salsabila Putri Supriyono; Kurniaty Atmia; Novita, Sheilla (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to design a prototype of an Internet of Things (IoT)-based temperature and humidity monitoring system. This tool is designed using the Blynk platform implemented in the Air Handling Unit (AHU) at Juwata Tarakan Airport. This system uses ESP32 as a microcontroller, DHT22 sensor, and OLED LCD and the Blynk application as monitoring media. In this research, I used the Research and Development (R&D) method with the stages of problem identification, design, testing, product revision, and conclusion. The test results show that the system can monitor temperature and humidity in real-time, provide automatic notifications when the temperature exceeds the threshold, and facilitate technicians in supervision without having to be physically present on site. This system can be applied not only at airports, but also in commercial buildings and other public facilities that require an efficient temperature and humidity monitoring system